Programmable Engineering of a Biosensing Interface with Tetrahedral DNA Nanostructures for Ultrasensitive DNA Detection1. Issue 7 (29th December 2014) - Lin, Meihua; Wang, Jingjing; Zhou, Guobao; Wang, Jianbang; Wu, Na; Lu, Jianxin; Gao, Jimin; Chen, Xiaoqing; Shi, Jiye; Zuo, Xiaolei; Fan, Chunhai
Abstract Self‐assembled DNA nanostructures with precise sizes allow a programmable "soft lithography" approach to engineer the interface of electrochemical DNA sensors. By using millimeter‐sized gold electrodes modified with several types of tetrahedral DNA nanostructures (TDNs) of different sizes, both the kinetics and thermodynamics of DNA hybridization were profoundly affected. Because each DNA probe is anchored on an individual TDN, its lateral spacing and interactions are finely tuned by the TDN size. By simply varying the size of the TDNs, the hybridization time was decreased and the hybridization efficiency was increased. More significantly, the detection limit for DNA detection was tuned over four orders of magnitude with differentially nanostructured electrodes, and achieved attomolar sensitivity with polymeric enzyme amplification.